Cover Image. Issue 4 (25th March 2018) - Li, Ji; Cao, Zhixian; Hu, Kaiheng; Pender, Gareth; Liu, Qingquan
Abstract : The cover image, by Ji Li et al., is based on the Research Article A depth‐averaged two‐phase model for debris flows over erodible beds, DOI: 10.1002/esp.4283 .